1996
DOI: 10.1002/(sici)1097-0142(19961015)78:8<1762::aid-cncr17>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of proliferating cell nuclear antigen, p53 protein and nm23 protein, and nuclear DNA content in transitional cell carcinoma of the bladder

Abstract: The tumor growth fraction as assessed by PCNA immunostaining is an independently significant predictor for survival of patients with TCC of the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Our results are consistent with several studies [12,29-31] which showed a significantly inverse correlation between reduced nm23-H1 expression and disease staging, histopathologic differentiation, tumor size, high risk of metastasis and reduced OS. However, some reports showed a positive correlation between nm23-H1 expression and tumor grading, muscle invasion or proliferating cell nuclear antigen expression, implying a positive growth regulatory role for nm23-H1 in bladder carcinogenesis [13,31,32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with several studies [12,29-31] which showed a significantly inverse correlation between reduced nm23-H1 expression and disease staging, histopathologic differentiation, tumor size, high risk of metastasis and reduced OS. However, some reports showed a positive correlation between nm23-H1 expression and tumor grading, muscle invasion or proliferating cell nuclear antigen expression, implying a positive growth regulatory role for nm23-H1 in bladder carcinogenesis [13,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of the nm23-H1 as a metastasis suppressor for human cancers including bladder is still controversial. Some studies demonstrated that nm23-H1 is inversely correlated with tumor staging, histological differentiation and clinical outcome [11,12], others showed a positive relationship to histological grading and muscle invasion [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Findings about the relationship between p53 overexpression and subsequent tumor recurrence or progression in superficial bladder carcinoma have been contradictory. Although some authors have shown an association of p53 overexpression with tumor progression,17 others have reported no association 18, 19. Mutations in the p53 gene are the most common genetic defect in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In urothelial carcinoma in situ and T1 and T1a urothelial carcinoma, an association between p53 overexpression and tumor progression has been reported, but other studies have not found this association. [21][22][23][24][25][26] The data regarding p53 protein content in inverted papilloma are limited. Two studies that examined p53 in inverted papillomas showed that most inverted papillomas had fewer than 30% p53 positive cells, but some neoplasms showed p53 staining similar to high grade in- vasive urothelial carcinomas; no clinical data were provided in these series.…”
Section: Discussionmentioning
confidence: 99%